Response of bioregulators and irrigation on plant height of Indian mustard (Brassica juncea L.) - Ajeet Singh; Ram Swaroop Meena (Journal of Oilseed Brassica, 2026)
The field experiment was carried out during the 2014-15 and 2015-16 in Rabi season to evaluate the response ofbioregulators and irrigation on growth parameters of Indian mustard (Brassica juncea L.). The treatments consistedthree irrigation levels (no irrigation, one irrigation and two irrigation) and seven foliar spray of bioregulators (control(water spray), thiourea @1000ppm, thiourea @ 500ppm, salicylic acid @ 100ppm, salicylic acid @ 50ppm, glycinebetaine@ 100ppm and glycinebetaine @ 50ppm). The result indicated that in the irrigated plots significantly improved the plantheight of Indian mustard. The application of two irrigation recorded highest plant height at 80 DAS (132.7, 119.9 and126.3 cm), 100DAS (173.6, 168.5 and 171.1 cm) and at harvest (176.4, 171.9 and 174.2 cm) followed by the application ofone irrigation in both years and pooled analysis, respectively. Moreover, the application of bioregulators significantlyimproves the plant height of the Indian mustard. The application of thiourea @ 1000ppm gave highest plant height at 80DAS (130.5, 118.2 and 124.4 cm), 100DAS (172.4, 166.8 and 169.6 cm) and at harvest (175.3, 170.9 and 173.1 cm). However,the application of thiourea @ 500 ppm was statistically at par with thiourea @ 1000ppm in both years and pooledanalysis, respectively. Furthermore, combined result of bioregulators and irrigation levels were observed significant onplant height of Indian mustard. The application of two irrigation+ foliar spray of thiourea @1000ppm recorded thehighest plant height at 100DAS (190.2, 182.3 and 186.3 cm) and at the time of harvest (194.2, 187.6 and 190.9 cm) overcontrol. The application of two irrigation+ foliar spray of thiourea @ 500ppm was statistically at par at 100 DAS (189.4,181.6 and 185.5 cm) and at harvest (193.3, 186.7 and 190.0 cm) with two irrigation+ foliar spray of thiourea @1000ppm inboth years and pooled analysis, respectively. The present study highlighted the practical importance of the irrigationlevels and foliar spray of bioregulators combination response on plant height of Indian mustard.